If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xy + w = 9 Reorder the terms: w + xy = 9 Solving w + xy = 9 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1xy' to each side of the equation. w + xy + -1xy = 9 + -1xy Combine like terms: xy + -1xy = 0 w + 0 = 9 + -1xy w = 9 + -1xy Simplifying w = 9 + -1xy
| -2.5y=-x+3.5 | | (3x-9)(5x+6)=0 | | -800=-20(-5b) | | -2.5=-x+3.5 | | h=-16t+64t-60 | | y-5=-7 | | 7n-2-4n= | | 1+4x=-43 | | 9+7x=-5 | | -5y=-x+3.5 | | 14+5n=-4+17 | | 7x+9=42 | | (x+f)+2=j | | -14+y=-17 | | 2-j=6-5j | | 1+6x=-47 | | 2m-10m=56 | | X^2+9-20=0 | | -8.48-6.4= | | -3x-3=-6 | | -2+8=6b-1-5b | | 17=-5(3+w)+7 | | 15x+1=y | | 7x+10=-116 | | -2(-c-8)=-2c-8 | | 3y+4(y-5)=15 | | 4(x+2)=3(2x+7) | | 2(a-3)=4a-(2a-6) | | 6-6=16t-6t | | 6a+10=3a+55 | | 4w-1=7(w+2) | | 2s-13s=55 |